Influence of endorser credibility on attitude and purchase intention among social networking sites (SNSs) users - Samat, Muhammad Faizal (2015)
Advertising has always been an important marketing tool for companies to promote their products to potential customers. The rapid evolution of technology has encouraged many companies to shift from traditional advertising medium to the new medium such as the Internet as their advertising channel. In this context, social networking site (SNS) advertising has become one of the most popular online advertising platforms on the Internet due to the large number of users or potential consumers in Malaysia present in the SNS. Marketers have so long devised various advertising strategies in order to penetrate the advertisement clutter and get consumers to notice them. Past studies have proven that using endorser in an advertisement effectively influenced the formation of a positive attitude among consumers and led to purchase intention in traditional medium. However, these studies tend to examine on the effectiveness of endorser on the traditional advertising medium. The focused of these studies was also on the interactivity and effectiveness of the new media as the new medium of advertising. Studies on effectiveness of the endorser and its influence on purchase intention and attitudes on online advertisements is very limited. Hence, this study attempts to address this gap by examining the influence of endorser credibility on attitude and purchase intention among social networking sites (SNSs) users. In addition, it also sought to determine the role of attitude towards SNS advertising and attitude towards the brand as mediator on the relationship between endorser credibility and online purchase intention. The role of gender as moderator was also examined. The theoretical framework of this study has been supported by two different theories which are Endorser Credibility Model and Affect Transfer Hypothesis (ATH). A total of 300 questionnaires were distributed in the Klang Valley, West Malaysia, but only 274 questionnaires were useable for further analysis. The data were analyzed using SPSS version 20.0 (Reliability, Validity, Descriptive, Normality, Multiple Regression, and Hierarchical Regression). Findings showed that a credible endorser leads the consumers to have an online purchase intention. In terms of attitude towards SNS advertising, consumers that perceive the endorser as credible develop a positive attitude towards the brand. In addition it was found that the higher the attitude towards the brand advertised, the higher their intention to purchase online. In terms of demographic factors, in Malaysia, gender does not play a moderating role. It signifies that, the effect of attitude towards brand and online purchase intention is not affected by gender of the online consumers. Men or women have the same interest in online shopping when they like the brand they are exposed to. However, to get a better understanding, further study can be done that covers the rural and urban area as the sample size. This study offered several implications for both academia and industry.